TATA KELOLA IT DENGAN MENGGUNAKAN METODE LUFTMAN STUDI KASUS : SEKOLAH SMK INFORMATIKA CIPUTAT - Triningsih, Triningsih (Informatik : Jurnal Ilmu Komputer, 2018)
Information technologi is growing rapidly And information technologi also provides adventages over a system that is running. The deveploment of information technologi also has an impact on the world of education, especially in schools that are useful to help learning activities. By maximizing the information technology in SMK Information Ciputat school open ooportunities for the progress of learning activities in the school